1997
DOI: 10.1128/jcm.35.3.679-684.1997
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of monoclonal antibodies specific for the lipopolysaccharide of Escherichia coli O157

Abstract: Identification of the O157 antigen is an essential part of the detection of Escherichia coli O157:H7, which is recognized as a major etiologic agent of hemorrhagic colitis. However, polyclonal antibodies produced against E. coli O157:H7 lipopolysaccharide (LPS) may react with several other bacteria including Brucella abortus, Brucella melitensis, Yersinia enterocolitica O9, Escherichia hermannii, and Stenotrophomonas maltophilia. We produced eight monoclonal antibodies (MAbs) specific for the LPS of E. coli O1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 37 publications
1
32
0
2
Order By: Relevance
“…Screening for the rfbE O157 gene was found more specific than O-serotyping, as cross-reactions described for Salmonella O30, Y. enterocolitica O9, Escherichia hermanii and Cit. freundii strains with an O157 antigen (Westerman et al 1997;Samuel et al 2004) were not found at the DNA-level. Similar findings were made for E. coli O111 group and the serologically cross-reacting Salmonella O35.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Screening for the rfbE O157 gene was found more specific than O-serotyping, as cross-reactions described for Salmonella O30, Y. enterocolitica O9, Escherichia hermanii and Cit. freundii strains with an O157 antigen (Westerman et al 1997;Samuel et al 2004) were not found at the DNA-level. Similar findings were made for E. coli O111 group and the serologically cross-reacting Salmonella O35.…”
Section: Discussionmentioning
confidence: 90%
“…These tested all negative as well as all strains belonging to other types of Enterobacteriacea. We have tested other enterobacteriaceal strains that were reported to have similarities in their O-antigen to E. coli O157 such as Salmonella O30 (n = 3), and one each of Yersinia enterocolitica O9, Escherichia hermannii and Citrobacter freundii serologically positive for the E. coli O157 antigen (Westerman et al 1997;Samuel et al 2004). All these tested negative for rfbE O157 gene indicating that the detection system is specific for the E. coli rfbE O157 gene.…”
Section: Detection Of Variants Of the Intimin (Eae-gene) Familymentioning
confidence: 99%
“…Monoclonal antibodies for the LPS of E. coli O157 have been described by two groups (Perry et al . 1988; Westerman et al . 1997).…”
Section: Discussionmentioning
confidence: 99%
“…(1988) did not present any results concerning cross reactions with bacteria that mimic the LPS of E. coli O157 on the MAbs that they developed. Those MAbs produced by Westerman et al . (1997) did not bind to the LPS of Y. enterocolitica O9 or Cit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation